Review of the genus Ommatoiulus in Andalusia, Spain (Diplopoda: Julida) with description of ten new species and notes on a remarkable gonopod struc-ture, the fovea - Akkari, Nesrine; Enghoff, Henrik (Zootaxa, 2012)
A comprehensive revision of the species of the genus Ommatoiulus in Andalusia, southern Spain, is carried out for thefirst time, revealing the presence of a total of 19 species, among which are one new record for the country, one for con-tinental Spain, two new records for Andalusia and 10 species new to science: Ommatoiulus baenai, O. baileyi, O. hoff-mani, O. jaenensis, O. kimei, O. pseudoflagellatus, O. recueroi, O. reipi, O. sabinarensis, O. schubarti n.spp. Thefollowing taxa are synonymised: Schizophyllum hoplites Verhoeff, 1910, S. diplurum appendiculatum Brolemann,1925, and Ommatoiulus diplurus mauriesi Hoffman, 1975, are regarded as junior synonyms of Ommatoiulus diplurus(Attems, 1903), n.syn. Schizophyllum dorsovittatum estrellanum Verhoeff, 1910, and S. calatravanum Brolemann,1920, are junior synonyms of Ommatoiulus dorsovittatus (Verhoeff, 1893), n.syn. Schizophyllum nivale Schubart,1959, is a junior synonym of Omnmatoiulus ilicis (Brölemann, 1896), n.syn. Full descriptions and diagnostic notes areprovided for all the species with accounts on their distributions, habitats, and notes discussing their taxonomy. A di-chotomous identification key, based on gonopod structures, is presented to facilitate species identification. In the dis-cussion section, the general patterns of species distribution are underlined, showing a clear tendency to ‘endemism’ forthe majority of species and to polymorphism for species with broader distribution ranges, especially O. diplurus. A dis-junct distribution Andalusia/Pyrenees is registered for O. ilicis. A comprehensive comparison of gonopods is attempt-ed, and three main types of gonopod configuration are delimited, denoting a wide range of structural complexity. Thefovea, a cavity in the posterior gonopods, is explored for the first time with scanning electron microscopy, revealing anagglutination of spermatozoa and confirming Verhoeff’s original observation dating back nearly 120 years. The con-stancy of the fovea in all Schizophyllini, combined with its absence in the rest of the julids, provides an additional apomorphy for the tribe.